(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe present research paper provides an analysis of Thomas Dekker’sexaltation of the figure of the Babylonian woman as a tragic heroine in his dramaticart. The paper falls into two sections. The first section outlines the deliberatemispresentation of the figure of the Babylonian woman in the Bible and themisreading of that figure. The second section reveals Dekker’s rectification of thedistorted image of the Babylonian woman, whom he defends and glorifies as aheroine and a victim of misinterpretation and conspiracy.